Investigating the Impact of Isolation During COVID-19 on Family Functioning – An Australian Snapshot - Sheen, Jade; Aridas, Anna; Tchernegovski, Phillip; Dudley, Amanda; McGillivray, Jane; Reupert, Andrea (Frontiers in Psychology, 2021)
This study explored possible changes in family functioning from the perspective of parents during the COVID-19 pandemic. Thirty-four parents/guardians of children under 18 years completed a semi-structured interview, average length 47 minutes. Interviews focussed on changes in different aspects of family functioning including family roles, routines and rules; parenting practices; communication and relationships; and strengths, challenges and tensions. Data were analysed using reflexive thematic analysis applied in an idiographic and inductive manner to reduce the loss of individual experiences and perspectives. Four superordinate themes were identified: shifting family roles and boundaries throughout the pandemic; impacts on routines and relationships; opportunities and resourcing; and, experiences of support and unity. Gender differences were evident across some themes, particularly changing roles, workload and work-home boundaries. Challenges and tensions were frequently highlighted, particularly by ‘vulnerable’ family groups such as those with children with disabilities. Parents also described a renewed sense of family and community, that underpinned adaptive coping responses. The results highlight the importance of family connectedness in times of need.